2023
DOI: 10.1021/acscatal.3c00986
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy-Rich TiO2 as an Efficient Non-noble Metal Catalyst toward Mild Oxidation of Methane Using Hydrogen Peroxide as the Oxidant

Abstract: Direct functionalization of methane remains a key challenge, especially for using non-noble metal catalysts. We demonstrated that TiO 2 nanorods with abundant oxygen vacancies enabled mild oxidation of methane by H 2 O 2 into formaldehyde (HCHO) without light irradiation. The activity of TiO 2 nanorods with the concentration gradient of oxygen vacancies (V O ) increased with the V O concentration. In H 2 O 2 aqueous solution under 30 bar of CH 4 at 70 °C for 1 h, the TiO 2 nanorods with the most abundant V O e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…15 To overcome the spin-forbidden limitation, the highly reactive metal center has been adopted to transfer electrons to molecular oxygen, leading to the excitation of the triplet to the singlet state, 14 but it is difficult to form highly reactive metal−oxo sites under mild conditions. To this end, various oxidants have been utilized, such as H 2 O 2 , 12,16,17 sulfur trioxide (SO 3 ), 13 and corrosive acids (e.g., oleum 18 and hydrobromic acid 19 ). The expensive nature of strong oxidants currently impedes their utilization.…”
mentioning
confidence: 99%
“…15 To overcome the spin-forbidden limitation, the highly reactive metal center has been adopted to transfer electrons to molecular oxygen, leading to the excitation of the triplet to the singlet state, 14 but it is difficult to form highly reactive metal−oxo sites under mild conditions. To this end, various oxidants have been utilized, such as H 2 O 2 , 12,16,17 sulfur trioxide (SO 3 ), 13 and corrosive acids (e.g., oleum 18 and hydrobromic acid 19 ). The expensive nature of strong oxidants currently impedes their utilization.…”
mentioning
confidence: 99%
“…Although TiO 2 photocatalysis may be a promising method for selective light alkane conversion under mild conditions, the active oxygen species for light alkane conversion via photocatalysis remains under debate. A series of experimental works conducted under ambient conditions support the idea that the hole-trapped lattice oxygen is the active species for the initial C–H bond activation of methane (CH 4 ) over ZnO, TiO 2 , and MgO catalysts. , However, mechanistic studies of light alkane (C1–C3) conversion on the model rutile (R) TiO 2 (110) surface ,, suggest that the hole-trapped oxygen adatom at the five-coordinated Ti 4+ site (Ti 5c , O Ti – ) is the active species for the initial C–H bond activation of light alkanes, which occurs via a hydrogen atom transfer (HAT) process .…”
mentioning
confidence: 99%
“…Since the first discovery of photoelectrocatalytic water (H 2 O) splitting into hydrogen (H 2 ) and oxygen (O 2 ) with Pt and TiO 2 semiconductor electrodes in 1972 by Fujishima and Honda, TiO 2 photocatalysis has intrigued a broad array of researchers for decades because of its potential applications in renewable clean energy. In thorough research, a TiO 2 -based catalyst has shown its potential in light alkane conversion under mild conditions. Although an enormous amount of attention has been focused on the fundamental processes of TiO 2 photocatalysis, a deep understanding of the fundamental processes (including charge/energy relaxation and transfer, breaking and formation of chemical bonds, etc.) underlying photocatalytic light alkane conversion is still lacking.…”
mentioning
confidence: 99%